Primary psychopathy and alcohol pathology in college students: The role of protective behavioral strategies. (2nd November 2017) - Kramer, Matthew P.; Stevenson, Brittany L.; Dvorak, Robert D.
ABSTRACT: Overview : Though not an official diagnosis, psychopathy has become an important area of research due to the litany of deleterious outcomes associated with this aspect of temperament. Psychopathy is composed of primary and secondary traits. Research consistently links psychopathy to alcohol pathology, though often only via secondary traits which are comprised of intractable aspects of behavior (e.g., poor impulse control). In contrast, primary psychopathy is comprised of behaviors that can be learned and thus may be more malleable (i.e., low harm reduction behaviors). Objectives : The current study examines associations between primary psychopathic traits and alcohol involvement as a function of Protective Behavioral Strategies (PBS) utilization in a sample of college students. Method : Participants ( n = 936 college student drinkers; 66.56% female) completed a series of questionnaires assessing primary psychopathy, alcohol involvement, and PBS use. Results : There was a significant positive association between primary psychopathy and alcohol consumption and pathology. This association was partially mediated via diminished PBS use. PBS use also moderated the relationship between alcohol consumption and pathology. The indirect effects from psychopathy to alcohol outcomes were attenuated at high (+1 SD ) PBS and potentiated at low (−1 SD ) PBS. Conclusion : The current findings suggest that some of the alcohol pathology associated with psychopathy is a function of lower harm reduction strategies among individuals with more psychopathic traits. These findings suggest that interventions targeting PBS use may be one way to reduce alcohol problems among those with higher levels of primary psychopathy.